Evaluation of the WPA2-PSK wireless network security protocol using the Linset and Aircrack-ng tools - Acosta López, Alberto; Melo Monroy, Elver Yesid; Linares Murcia, Pablo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 73-80).